There Is a Limit to Your Openness: Mental Illness Stigma Mediates Effects of Individual Traits on Preference for Psychiatry Specialty - Fino, Edita; Agostini, Alessandro; Mazzetti, Michela; Colonnello, Valentina; Caponera, Elisa; Russo, Paolo Maria (Frontiers in Psychiatry, 2019)
Objective: The widening gap between the need for mental health professionals and low percentages of medical students pursuing psychiatric career, urges an examination of how individual traits and attitudes interact in order to better explain the variance in preference for psychiatry as a specialty choice. Methods: The target population included medical students attending the second year of medical education program, at Bologna University. Participants completed an online questionnaire evaluating preference for psychiatry specialty (one single item and a scenario based response), personality traits (the Big Five Questionnaire), attitudes (Mental Illness for Clinician, MICA-2), behaviors (Reported and Intended Behavior Scale, RIBS) and fears towards mental illness (questionnaire created ad hoc). Socio-demographic data were also collected. Results: A total of 284 medical students (58.8% female, mean (SD) age 20.47± 1.90) completed the questionnaire. Preference for psychiatry specialty, was significantly and positively associated with Openness to experience, and negatively related with MICA-2 and RIBS. The full mediation model provided good indices explaining 18 % of the variance. Mental illness stigma was strongly and negatively associated with both openness to experience and preference for psychiatry and the mediation results evidenced a positive and significant effect. Conclusions: Mental illness stigma influences psychiatry choice netting out effects of openness to experience. Stigma awareness and reduction programs should be introduced as early as possible in medical education.